Does the application of growth bioregulators improve the foliar concentration of nutrients, non-structural carbohydrates and yield in pecan? - Laura Raquel Orozco Meléndez; Ofelia Adriana Hernández Rodríguez; Oscar Cruz Alvarez; Adalberto Benavides Mendoza; Marisela Calderón Jurado; Damaris Leopoldina Ojeda Barrios (Ciência e Agrotecnologia, 2021)
ABSTRACT Carya illinoinensis (Wangenh.) K. Koch. is a deciduous fruit species with high economic impact and nutritional value that exhibits alternate bearing behavior. In this study, the concentration of foliar nutrients, non-structural carbohydrates and yield were evaluated in cultivar Western Schley pecan in response to the foliar application of gibberellic acid (50 mg L-1 GA3), prohexadione calcium (500 mg L-1 PCa) and thidiazuron (10 mg L-1 TDZ).The statistical analysis reveals that between agricultural cycles, the treatments showed no variation in the foliar concentration of nitrogen total (N-total), potassium (K), calcium (Ca), magnesium (Mg), iron (Fe), copper (Cu), manganese (Mn) and non-structural carbohydrates (fructose, glucose, sucrose and starch). However, the application of PCa showed no significant effect on the concentration of phosphorus (P) (1.5 and 1.9 g kg-1). On the other hand, the concentration of zinc (Zn) (27.0-60.1 mg kg-1) showed a significant difference between years, with no effect due to the application of growth bioregulators. The trees treated with GA3 minimized alternate bearing by presenting similar values (12.4 and 15.3 kg tree-1) of yield. Likewise, the applied treatments did not affect the nut weight per kilogram (kg) (5.5-6.8 g) and kernel percentage (56.5-60.8). These data provide a new perspective on the complex nature of alternate bearing production in cultivar Western Schley pecan and are interpreted to indicate that alternate production could be regulated by carbohydrate reserve, nutrient concentration, and gibberellins.